In memory of Vasyl Vasylyovych Zhmurko, scientist and teacher - Editorial Team (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія, 2022)
In memory of Vasyl Vasylyovych Zhmurko, scientist and teacher